Proses Pelaksanaan Pengangkatan Anak Dan AkibatHukum Terhadap Pengangkatan Anak(Studi Kasus di Pengadilan Negeri Surakarta) - Maharani, Rinda Lucy, Nuswardhani, SH., S.U (2017)
This research aims to know the process of the implementation of the adoption on the basis of legislation in force in Indonesia, as well as to know the legal consequences of the appointed. The method of the approach that the author shared juridical normative approach is. The type of research used in this study the author is using this type of descriptive research Location research in the District Court of Surakarta. Method of data collection in this research study using the techniques of field studies and libraries. Based on the results of the research and the discussion then it can be inferred that the implementation process of adoption the child there are 3 stages of IE. Stages before he did the adoption of the child. Phase of the adoption. The recording phase of adoption. In addition there are also legal consequences arising against the son after the lift, i.e., will cause the legal relationship between the adoptive parents with adopted children, so equally give rise to rights and obligations.